Inventory Of Meat Randang Recipes In Batipuh Kabupaten Tanah Datar - Cindy Oki Syafira; Wirnelis Syarif (Jurnal Pendidikan Tata Boga dan Teknologi, 2021)
The purpose of this study was to make an inventory of the various types of beef randang recipes which include ingredients, spices, equipment and processing processes in Batipuh Tanah Datar Regency. This research is motivated by the absence of data explaining the various kinds of meat randang recipes in Batipuh, Tanah Datar Regency and as a first step in maintaining the national culture in promoting local traditional food as a tourist destination. This type of research is qualitative. Data collection techniques by means of observation, interviews, and documentation. Data analysis used in the field is reduction, display, conclusion and verification. The results of this study were 9 recipes of beef randang in Batipuh Tanah Datar, to be precise in Nagari Baripuh Ateh, Nagari Gunung Rajo, and Nagari Tanjung Barulak. Generally, the main ingredients used are beef and coconut milk from old coconut using wet spices, namely onions, garlic, ground chilies, ginger, galangal, lemongrass stalks, and dry spices, namely coriander, cloves, and nutmeg. And the leaves are lime leaves, turmeric leaves, and bay leaves. The tools used are plastic com, filter, cutting board, millstone and blender, stale skillet, sanduak and stove, samba plate, cambuang and pan. The processing of different spices with stove fuel and firewood.